Effects of Diminished NADPH:cytochrome P450 Reductase in Human Hepatocytes on Lipid and Bile Acid Homeostasis - Heintze, Tamara; Wilhelm, Denise; Schmidlin, Thierry; Hofmann, Ute; Zanger, Ulrich M.; Schwab, Matthias; Klein, Kathrin (Frontiers in Pharmacology, 2021)
NADPH:cytochrome P450 oxidoreductase (POR) is the obligate electron donor for microsomal cytochrome P450 (CYP) enzymes involved in biosynthesis of endogenous substances like bile acids and other steroids as well as in oxidative metabolism of xenobiotics. POR also supports other redox enzymes in fatty acid and cholesterol pathways. Recently, we established CRISPR/Cas9-mediated POR knockdown in the human hepatic cell model, HepaRG, and demonstrated differential effects of limited POR expression on CYP activity. The aim of the present work was to systematically investigate the impact of POR knockdown with focus on the expression of ADME (absorption, distribution, metabolism, and excretion) genes and related regulators. Functional consequences have been assessed using quantitative mass spectrometry for targeted metabolomics covering bile acids, cholesterol and its precursors, and for untargeted proteomics. In addition to previously described alteration of RNA expression of CYP genes, we showed significant downregulation of transcriptional regulators of drug metabolism and transport, including NR1I3 (CAR), NR1I2 (PXR), NR1H4 (FXR), NR1H3 (LXRα) in cells with POR gene disruption. Furthermore, POR knockdown resulted in deregulated bile acid and cholesterol biosynthesis demonstrated by low levels of cholic acid derivates and increased concentrations of chenodeoxycholic acid derivates, respectively. Systemic effects of POR knockdown on global protein expression were indicated by downregulation of several metabolic pathways including lipid metabolism and biological oxidation reactions. The deduced protein network map corroborates CYP enzymes as direct interaction partners, whereas changes in lipid metabolism and homeostasis are the result of indirect effects. In summary, our results emphasize a widespread role of POR in various metabolic pathways and provide first human data on the effects of diminished POR expression on drug and endogenous metabolism in a genome edited HepaRG cell model.